Analisis Kemampuan Pemecahan Masalah Siswa Pada Materi Geometri Berdasarkan Level Berpikir Van Hiele Kelas VIII SMPN 2 Wanasaba Tahun Ajaran 2020/2021 - Era Wati Sugara; Nyoman Sridana; Eka Kurniawan; Baidowi Baidowi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The purpose of this study was to describe students' problem-solving abilities on geometry material based on Van Hiele's level of thinking in class VIII of SMPN 2 Wanasaba in the 2020/2021 school year. The method used in this study are tests and interviews. The results showed that the thinking level of students in class VIII D of SMP Negeri 2 Wanasaba was generally dominant at level 0 (visualization), as many as 13 people (48.14%) of the 27 students who took the test. In solving geometry problems according to Polya's stages, students who are at level 0 (visualization) have been able to do the stage of understanding the problem well but are still not perfect in making plans and implementing settlement plans. Students at level 1 (analysis) have been able to carry out the stages of understanding the problem, making plans and implementing plans, but in the stage of reviewing, students are not able to re-examine the results of the completion. Students at level 2 (informal deduction) are able to carry out the stages of understanding the problem, making plans, implementing a settlement plan and looking back even though they are not perfect at the stage of looking back. Students at level 3 (deduction) have very good problem solving skills, they are able to carry out the stages of understanding the problem, making plans, implementing plans and looking back appropriately and the calculation process is also carried out correctly. This shows that the higher the Van Hiele thinking level of the students, the better their geometric problem solving abilities will be.